ChemInform Abstract: Pressure‐Induced Phase Transition of SnH4: A New Layered Structure. Issue 15 (24th March 2016) - Zhang, Huadi; Jin, Xilian; Lv, Yunzhou; Zhuang, Quan; Li, Ying; Bao, Kuo; Li, Da; Liu, Bingbing; Cui, Tian
Abstract: A new phase of SnH4 with C2/m symmetry is predicted by first‐principle calculations using the Vienne ab initio simulation package (VSAP code) at pressures <400 GPa.